Women, Family and Property. Economic Management of Family Wealth by Female Heads of Household. Melipilla (Chile), 1810-1837; [Mujeres, Familia y Propiedad. Gestión Económica del Patrimonio Familiar por Mujeres Jefas de Hogar. Melipilla (Chile), 1810-1837] - Goicovic-Donoso, I (Universidad de Chile, Facultad de Filosofia y Humanidades, Departamento de Literatura, 2024)
The aim of this article is to analyze the family wealth management strategies deployed by women around Melipilla (Chile) during the 1810-1837 period. We have been able to establish that this period was particularly complex in the lives of both popular and elite families, due to the contingencies imposed by the War of Independence and the civil conflicts associated with the construction of the State. Despite this, women who found themselves alone, due to the recruitment, escape or imprisonment of their husbands, fathers, or sons, managed to carry out different initiatives of wealth management, such as the purchase, sale and lease of land, houses and belongings, as well as the development of small productive and commercial enterprises. This work was based on notarial and judicial sources, contained in the National Historical Archive. © 2024 Universidad de Chile, Facultad de Filosofia y Humanidades, Departamento de Literatura. All rights reserved.